2016
DOI: 10.1016/j.idcr.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 and HIV-1 co-infection: A case report and review of the literature

Abstract: HTLV type 1 and 2 are both involved in actively spreading epidemics, affecting over 15 million people worldwide. HTLV-1 has been described as the more clinically significant one, being associated with diseases such as adult T-cell leukemia and tropical spastic paraparesis. We report here a case of tropical spastic paraparesis in an HIV-positive patient who did not report any history of travel or residence in an HTLV endemic area.A 57 year old African-American male was admitted to the hospital due to bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
(21 reference statements)
0
15
0
1
Order By: Relevance
“…In European and United States studies, individuals with HIV-1 and HTLV-2 co-infections were found to result in altered clinical outcomes, and also delayed development of AIDS [55, 56]. In contrast, there are several reports were indicated that co-infection with HTLV-1/HIV-1 is associated with faster AIDS clinical progression and shorter survival time and also have more risk to progress myelopathies as well as neurological disease [54, 55, 57, 58]. HTLV-I is widespread in a variety of geographic regions, including Japan, the Caribbean, South America, Africa and Northeastern Iran [59–61].…”
Section: Discussionmentioning
confidence: 99%
“…In European and United States studies, individuals with HIV-1 and HTLV-2 co-infections were found to result in altered clinical outcomes, and also delayed development of AIDS [55, 56]. In contrast, there are several reports were indicated that co-infection with HTLV-1/HIV-1 is associated with faster AIDS clinical progression and shorter survival time and also have more risk to progress myelopathies as well as neurological disease [54, 55, 57, 58]. HTLV-I is widespread in a variety of geographic regions, including Japan, the Caribbean, South America, Africa and Northeastern Iran [59–61].…”
Section: Discussionmentioning
confidence: 99%
“…Although T cells are the major targets of both HIV and HTLV-I, however, these viruses present a different biological behavior that causes diverse impacts on host immunity and ultimately leads to numerous clinical diseases [ 39 ]. It has been reported that the HTLV-I co-infection rate among HIV infected patients as increase as 100 to 500 times in comparison with the general population [ 40 ]. In seroepidemiologic studies, it has been recorded that HIV-infected patients are more exposure to be co-infected with HTLV-I, and vice versa compared to the general population [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the natural history of HIV, many researchers have noted that co-infection with HIV and HTLV-I can accelerate the clinical progression to AIDS. On the other hand, HIV can adjust HTLV-I expression in co-infected individuals which leads them to a higher risk of developing HTLV-I related diseases such as ATL and TSP/HAM [ 40 , 41 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the dual infection rates in peoples living in some parts of Brazil have reached 16% of HIV-infected patients [41]. In a recent work, it has been estimated that the HIV single infected patients have more exposure to be dual infected with HTLV-I at a higher rate initiating from 100 to 500 times in comparison with the uninfected peoples [42]. Moreover, some seroepidemiologic studies have reported that HTLV-infected patients are at risk to have a concurrent infection with HIV, and vice versa compared to those who are infection-free from the general population [40].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that HIV infected individuals who are possibly dual infected with HTLV-I can potentially be associated with clinical progression with AIDS. In contrast, HIV can modify HTLV-I expression in dual infected patients which leads them to a higher risk of developing HTLV-I related diseases such as TSP/HAM and ATL [40,42].…”
Section: Introductionmentioning
confidence: 99%